Fun with Fruits Menggunakan Metode Make A Match Pada Peserta Didik Sekolah Dasar - Mbupu, Oktaviana; Pali, Agustina; Dhou, Maria Konstiana Wea; Kami, Wihelmina Nirini Wula; Kwen, Yohanes Ola; Patitio, Rafael Dianus (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2025)
This Community Service Activity (PKM) aims to improve English comprehension in Class 1 of SD Inpres Wolowona 2 on the topic of fruits. Initial observations showed that the comprehension of class 1 students in English subject was still low, this was caused by the lack of interesting learning methods and media. To overcome this, the community service team implemented the Make A Match method combined with game playing and singing activities. The learning process that actively involves student through a game of chance pictures with words related to the basics of English and singing simple English songs. The results obtained showed an increase in student’s learning skills and motivation. The approach used was able to create a fun and interactive learning atmosphere so that it helps students understand the fruits material well. This PKM activity is espected to be able to add innovative English learning methods at the Elementary School level